Mechanical Properties of Pineapple Leaf Fibre Reinforced Polypropylene Laminated Composites - Md Rejab, Mohd Noor Arib (2004)
Pineapple leaf fibre which is rich in cellulose,relatively inexpensive and abundantly available has the potential to be used as reinforcement in polymer composite.The present research investigates the tensile, flexural and impact behaviours of pineapple leaf fibrepolypropylene(PALF-PP) composites as a function of volume fraction.Composites specimens with the dimensions of 115 mm x 19 mm and 127 mm x 12.7 mm were cut from the 3 mm thickness laminates to determine tensile and flexural properties using an Universal Testing machine. Specimen with dimensions 63.5 x 12.7 x 3.0 mm were used for Izod impact test was using a TMI pendulum tester The tensile modulus and tensile strength of the composites were found to be increased with fibre content in accordance with the rule of mixtures. The tensile modulus and tensile strength with a volume fraction 10.8 % are 687.02 MPa and 37.28 MPa respectively. The flexural modulus gives higher value at 2.7 % volume fraction.The flexural strength of the composites containing 5.4 % volume fraction was found to be higher than that of pure polypropylene resin by 5.1 %. At 2.7 % volume fraction,the work of fracture is about 6.1 % higher than that of virgin polypropylene. However, at higher percentage volume fraction (5.4 %, 10.8 % and 16.2 %) the work of fracture decrease by about 19.2 % and then 2.7 % of volume fraction.The reasons why flexural and impact properties gave lower values for volume fraction above 5.4 % are possibly due to the fibre-to-fibre interaction,void and dispersion problems. This was confirmed by the micrographs of scanning electron microscopic (SEM).Studies on SEM micrographs were carried out to understand the fibre –matrix adhesion and fibre breakage